Two New Species of Scleria section Hypoporum (Cyperaceae) from Espírito Santo, Brazil - Mayedo, Waldo Bonet; Thomas, William Wayt (Phytotaxa, 2016)
Two species of Scleria section Hypoporum from the state of Espírito Santo, Brazil, are described, illustrated, mapped, and compared to two similar species, S. virgata and S. variegata. While most species of sect. Hypoporum are small and narrow-leaved, these two species are robust.